2022
DOI: 10.3390/v14020221
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Salivary Proteins from Aedes aegypti Mosquito Bind to the Zika Virus Envelope Protein

Abstract: Aedes aegypti mosquitoes are important vectors of several debilitating and deadly arthropod-borne (arbo) viruses, including Yellow Fever virus, Dengue virus, West Nile virus and Zika virus (ZIKV). Arbovirus transmission occurs when an infected mosquito probes the host’s skin in search of a blood meal. Salivary proteins from mosquitoes help to acquire blood and have also been shown to enhance pathogen transmission in vivo and in vitro. Here, we evaluated the interaction of mosquito salivary proteins with ZIKV b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Together, these studies suggest the potential role of antigen 5-like proteins in blood acquisition. In a recent study, Valenzuela-Leon et al (2022) found that a member of this family bound to the Zika virus envelope protein with nanomolar affinities. However, this interaction had no effect on viral replication in cultured endothelial cells and keratinocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these studies suggest the potential role of antigen 5-like proteins in blood acquisition. In a recent study, Valenzuela-Leon et al (2022) found that a member of this family bound to the Zika virus envelope protein with nanomolar affinities. However, this interaction had no effect on viral replication in cultured endothelial cells and keratinocytes.…”
Section: Resultsmentioning
confidence: 99%
“…ADA2 also removes adenosine from bite site and aids in a prolonged blood-feeding [ 45 ] and has been shown to partially enhance dengue and Zika virus infection in human THP-1 cells [ 3 ]. Recently, apyrase was shown to directly interact with ZIKV [ 46 ]. The above analysis suggests the importance of 1) the interactions of vector SGPs such as ADA2, D7 proteins (AAEL006424 and AAEL006417 ), apyrase, and aegyptin, with host receptors and 2) the interaction of some SGPs with the pathogen/host molecules.…”
Section: Discussionmentioning
confidence: 99%
“…AaVA-1 is a crucial target that promotes DENV and ZIKV infection in vitro in human THP-1 cells and in vivo in mouse models via interaction with human leucine-rich pentatricopeptide repeat-containing protein (LRPPRC) [ 3 ]. Recently, AaVA-1 was shown to directly interact with ZIKV [ 46 ]. This suggests the potential role of AaVA-1-CD4 and AaVA-1-DC-SIGN interactions on viral infection in human hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The human cell line HEK293 was used to recombinantly express 18 Ae. aegypti recombinant proteins, as described previously ( 20 ). After identification of the most immunogenic proteins, the production of AeApyrase, AeD7L1, AeD7L2, NIH-23, and NIH-27 was scaled up, and they were codon-optimized for mammalian expression, synthesized with a carboxyl-terminal HIS-tag (GenScript, Piscataway, NJ, USA), and cloned into pHEK293 Ultra Expression Vectors (Takara, Mountain View, CA, USA).…”
Section: Methodsmentioning
confidence: 99%